An analysis of serious adverse drug reactions at a tertiary care teaching hospital - Prajapati, Kinjal (Perspect Clin Res, 2016)
OBJECTIVE: The objective of this study was to analyze the various aspects of serious adverse drug reactions (serious ADRs) such as clinical presentation, causality, severity, and preventability occurring in a hospital setting. MATERIALS AND METHODS: All serious ADRs reported from January 2010 to May 2015 at ADR Monitoring Centre, Department of Pharmacology, B. J. Medical College and Civil Hospital, Ahmedabad, were selected as per the World health Organization –Uppsala Monitoring Center (WHO-UMC) criteria. A retrospective analysis was carried out for clinical presentation, causality (as per the WHO-UMC scale and Naranjo's algorithm), severity (Hartwig and Siegel scale), and preventability (Schumock and Thornton criteria). RESULTS: Out of 2977 ADRs reported, 375 were serious in nature. The most common clinical presentation involved was skin and appendageal disorders (71, 18.9%). The common causal drug group was antitubercular (129, 34.4%) followed by antiretroviral (76, 20.3%) agents. The criteria for the majority of serious ADRs were intervention to prevent permanent impairment or damage (164, 43.7%) followed by hospitalization (158, 42.1%). Majority of the serious ADRs were continuing (191, 50.9%) at the time of reporting, few recovered (101, 26.9%), and two were fatal. The majority of serious ADRs were categorized as possible (182, 48.8%) followed by probable (173, 46.1%) in nature. CONCLUSION: Antitubercular, antiretroviral, and antimicrobial drugs were the most common causal drug groups for serious ADRs. This calls for robust ADR monitoring system and education of patients and prescribers for identification and effective management.